Polymorphisms in cathepsin b is associated with growth in Asian seabass - Shadame Yeo; Joey Wong; Y.X. Tay; Zituo Yang; Le Wang; Fei Sun; May Lee; Yanfei Wen; Gen Hua Yue (Aquaculture and Fisheries)
This study investigates the relationship between polymorphisms in the cathepsin B (ctsb) gene and body weight in Asian seabass (Lates calcarifer). Despite the economic significance of this species, the genetic factors that influence growth performance in fish remain poorly understood. CTSB, a lysosomal cysteine protease involved in protein degradation and tissue remodelling, is a crucial regulator of growth. We analysed the full-length cDNA of ctsb and mapped it to the major quantitative trait locus (QTL) for growth on linkage group 2 in L. calcarifer. Single nucleotide polymorphisms (SNPs) within ctsb were identified and their associations with body weight were analysed in 298 individuals. Results revealed that SNP1 (C > T) in intron 2 of ctsb was significantly correlated with body weight. Quantitative real-time PCR (qRT-PCR) showed that ctsb was expressed in all tissues, with the highest expression in the gills and kidney of developing seabass. Knockdown/overexpression of ctsb in cell lines respectively promoted/inhibited cell proliferation without altering cell size. These findings suggest that ctsb plays a significant role in growth regulation in Asian seabass. This study provides a potential molecular marker for selecting fast-growing Asian seabass. Future research should focus on identifying causal variants in ctsb associated with accelerated growth, conducting in vivo studies, and exploring related signalling pathways.